Imaging the elusive anomalous origin of left coronary artery from pulmonary artery. Issue 11 (29th June 2017) - Sasikumar, Deepa; Sasidharan, Bijulal; Dharan, Baiju S.; Sivasankaran, Sivasubramanian; Krishnamoorthy, Kavasseri M.
Abstract : A 7‐year‐old girl with severe mitral regurgitation and pulmonary artery hypertension with good ventricular function was planned for mitral valve repair, but was subsequently diagnosed to have anomalous left coronary artery from pulmonary artery. We describe the pitfalls in the diagnosis of this rare anomaly, particularly in the presence of severe pulmonary artery hypertension and absence of circumstantial evidence of coronary steal and ventricular dysfunction.